Lexical Bundles Ending in that in Academic Writing by Czech Learners and Native Speakers of English - Gabriela Brůhová; Kateřina Vašků (Anglica. An International Journal of English Studies)
The aim of this paper is to explore how Czech learners of English use lexical bundles ending in that in their academic texts in comparison with novice and professional L1 authors. The analysis is based on three corpora (VESPA-CZ, BAWE and our own corpus of papers published in academic journals). The results suggest that Czech learners of English do not use a more limited repertoire of lexical bundles ending in that than professional writers. However, there are differences between the groups studied, especially in the range of various shell nouns used in nominal bundles. Novice writers, both L1 and L2, use bundles ending in that to express stance more frequently than professional writers.